Climate Organization With Employee Satisfaction Implementation - Desy Octaviani Indra; Andi Suswani; Nurlina (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2019)
Nurses are health workers who dominate as a whole and as the first and longest established contact with customers (patients and families) so that they need serious attention from the hospital management. The job satisfaction of health workers can be influenced by the organizational climate. This study aims to determine the relationship of the organizational climate with the job satisfaction of nurses in the inpatient room of RSUD H. Andi Sulthan Daeng Radja, Bulukumba Regency. This research is an analytic observational study with a cross-sectional approach. Sampling was done by a stratified random sampling technique. The population in this study were nurses in the inpatient room of H.Andi Sulthan Daeng Radja Hospital, Bulukumba Regency, as many as 218 people. The sample in this study was 87 people. The measuring instruments used were questionnaires and observations. Data analysis used with the Chi-Square test. The results of the respondents 'perceptions of the organizational climate are good categories with satisfied job satisfaction as many as 59 respondents (86.76%), and organizational climate of less categories with satisfied job satisfaction, namely 9 respondents (13.23%), while respondents' perceptions of organizational climate less categories with less satisfying job satisfaction as many as 15 respondents (78.94%), and less satisfied category job satisfaction, namely 4 respondents (21.05%). Based on the results of the analysis using the Chi-Square test statistic test obtained p-value <0.002 which indicates the existence of organizational climate relations with the job satisfaction of the nurses in the inpatient room of H. Andi Sulthan Daeng Radja Hospital, Bulukumba District.